Analisa Perdagangan Bebas Indonesia Dengan Singapura Dalam Pemenuhan Kebutuhan Pangan Singapura Serta Potensi Dan Ancamannya Bagi Indonesia Studi Kasus Sektor Peternakan - Fadhilah Ikhwanti; Garnis Fitria Aulia; Daspar (CV. ITTC INDONESIA, 2024)
There are good relations between Indonesia and Singapore regarding food needs. The relationship between Indonesia and Singapore has made these two countries establish strategic cooperation in several aspects of trade. In 2022, there was an increase in the value of bilateral trade which reached US 33.8 billion or an increase of 24.6% compared to 2021. Based on this data, it can be seen that in terms of trade, Singapore is the largest trading partner country in ASEAN for Indonesia. The government continues to increase cooperation to increase the value of Indonesian exports to Singapore and collaborate in various industrial sectors. In this case, the government needs to implement export regulations in the livestock sector to maintain stable domestic supplies and fulfill commitments in fulfilling export supplies to Singapore. Indonesia also needs to carry out strict supervision of producers in fulfilling export standards for processed meat food raw materials in accordance with Singapore Food Agency (SFA) standards. Indonesia's abundant natural resources represent extraordinary potential that can provide income for the community. The potential must be maximized by maintaining the quality and durability of the products owned so that they can compete in the global market.